Multiplication Of Pisang “Agung” (Musa Paradisiaca L.) With In Vitro As A Local Product For Food Security - Fatechan, Billy; Hazmi, Muhammad; Murtiyaningsih, Hidayah (Universitas Muhammadiyah Jember, 2024)
Pisang “Agung”(Musa paradisiaca L.) is one of the banana varieties originating from Lumajang Regency. Pisang Agung is famous for its large fruit and sweet taste. The conventional way of propagating Pisang “Agung” takes a long time, produces few shoots, is not uniform and is not guaranteed to be disease-free, these obstacles can be overcome by using tissue culture. The design that will be used in this study is a Non-Factorial Completely Randomized Design (CRD) consisting of 100 ppm BAP (B) which consists of 4 levels, namely B0 (0 ppm), B1 (3 ppm), B2 (6 ppm), B3 (9 ppm). The parameters observed were the age of shoot emergence, shoot height, number of shoots. The results showed that the treatment of various concentrations of BAP gave a significant effect on all observation parameters with the best treatment B3 age of bud emergence (9.25 days), bud height is B3 (7.35 cm) and the number of buds is B0 (3.90 pieces)